Holismo e testabilidade de teorias científicas: uma análise da tese Duhem-Quine - Araújo, Marcus Renato Alves (2005)
This is a study on Duhem-Quine thesis. Its purpose was to investigate epistemological differences and affinities between the holistic positions of Willard Quine and Pierre Duhem. This analysis showed that two quite different interpretations of Duhem-Quine thesis are possible: a weak version, argued by Duhem, and a strong version, more radical, argued by Quine in his article Two dogmas of empiricism. The study of holism, in this perspective, highlighted the importance of this subject to the Philosophy of Science and Language and how this approach can shed light on important philosophical issues, such as the relationship between scientific observations and theories; the thesis of the empirical underdetermination of theories; the theory-ladenness of observation sentences; the theory choice process; the inscrutability of reference; the theory of linguistic learning; among others.